Epilepsy: Asia versus Africa. - (:unkn) unknown (My University, 2014)
: Is epilepsy truly an "African ailment"? We aimed to determine this, since international health agencies often refer to epilepsy as an African disease and the scientific literature has spoken the same tone. Various published materials, mainly reports, articles, were used to gather Asian and African evidence on various aspects of epilepsy and many of its risk and associated factors. Our results suggest that in no way can epilepsy be considered as an African ailment and such characterization is most likely based on popular beliefs rather than scientific evidence. In comparison to Africa, Asia has a 5.0% greater burden from all diseases, and is 17.0% more affected from neuropsychiatric disorders (that include epilepsy). Given that more countries in Asia are transitioning, there may be large demographic and lifestyle changes in the near future. However these changes are nowhere close to those expected in Africa. Moreover, 23 million Asians have epilepsy in comparison to 3.3 million Africans and 1.2 million sub-Saharan Africans. In comparison to Africa, Asia has more untreated patients, 55.0% more additional epilepsy cases every year, because of its larger population, with greater treatment cost and possibly higher premature mortality. Of several associated factors discussed herein, many have more importance for Asia than Africa. The current state of epilepsy in Asia is far less than ideal and there is an urgent need to recognize and accept the importance of epilepsy in Asia. In no way can epilepsy be considered as an African ailment. This is most likely based on popular beliefs rather than scientific evidence. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.
Keywords: African Research